ADOPTING AI FOR COMPETITIVE ADVANTAGE IN INTERNATIONAL MANAGEMENT - Karimova Sogdiana Saxibjanovna (Western European Studies, 2024)
Adoption of artificial intelligence to ensure competitive advantage in international management has become one of the important tasks for every organization today. Rapid changes in the global economy, increased competition and changes in customer demands encourage organizations to seek innovative solutions. And artificial intelligence technologies play an important role in this process. This article examines how artificial intelligence can help provide competitive advantage in international management, its benefits, challenges, and future prospects.
Keywords: artificial intelligence; companies; computer programs